THE EFFECT OF PROBLEM BASED LEARNING (PBL) ASSISTED BY GEOGEBRA ON MATHEMATICAL PROBLEM SOLVING ABILITY - Putri Andriani; Ratih Handayani (Hipotenusa Journal of Research Mathematics Education (HJRME), 2026)
This study examines the effect of implementing a GeoGebra-assisted Problem Based Learning (PBL) model on students mathematical problem solving abilities. It was motivated by students low initial performance in solving problems, as indicated by pretest scores below the minimum mastery criterion, highlighting the need for innovative, technology integrated instruction. This study adopted a quantitative method employing a quasi experimental design with a pretest posttest control group. The participants were 42 seventh grade students at SMP Negeri 2 Abung Surakarta, with 22 in the experimental group (Class VII A) and 20 in the control group (Class VII B), selected via purposive sampling. The intervention spanned five sessions on the topic of squares, with the experimental group receiving GeoGebra assisted PBL instruction and the control group receiving conventional teaching. Data were collected through problem solving tests and analyzed using normality and homogeneity tests, N-gain analysis, and independent samples t-tests. Results showed that the experimental group achieved a higher average N-gain (0.608) than the control group (0.444), and the t-test indicated a significant difference , ? = 0.05). These findings confirm that the GeoGebra assisted PBL model effectively enhances students mathematical problem solving skills and supports the use of technology integrated learning in teaching squares at the junior high school level.